Efficacy, safety and dose–response relationship of teneligliptin, a dipeptidyl peptidase‐4 inhibitor, in Japanese patients with type 2 diabetes mellitus. Issue 9 (7th April 2013) - Kadowaki, T.; Kondo, K.
Abstract Aim To assess the efficacy, safety and dose–response relationship of once‐daily teneligliptin, a novel dipeptidyl peptidase‐4 inhibitor, in Japanese patients with type 2 diabetes mellitus (T2DM) inadequately controlled with diet and exercise. Methods In this randomized, double‐blind, placebo‐controlled, parallel‐group study, patients (n = 324) were randomized to receive teneligliptin 10, 20 or 40 mg, or placebo, once daily before breakfast for 12 weeks. The primary endpoint was the change in haemoglobin (Hb)A1c from baseline to week 12. Results All teneligliptin‐treated groups showed significantly greater reductions in HbA1c and fasting plasma glucose (FPG) than did the placebo group. The differences between the teneligliptin 10, 20 or 40 mg groups and the placebo group for the change in HbA1c were −0.9 [least‐squares (LS) mean; 95% confidence interval: −1.0, −0.7], −0.9 (−1.1, −0.7) and −1.0 (−1.2, −0.9)%, respectively (all, p < 0.001). The respective LS means for FPG were −17.8 (−23.4, −12.1), −16.9 (−22.6, −11.2) and −20.0 (−25.7, −14.3) mg/dl (all, p < 0.001). There were no significant differences in HbA1c among the three doses of teneligliptin. The incidence of adverse events and adverse drug reactions was similar in each group. The incidence of hypoglycaemia was not significantly different among the four groups. Conclusions Treatment with teneligliptin for 12 weeks provided significant and clinically meaningful reductions in HbA1c and FPG across the dose range studied and was generally well tolerated in Japanese patients with T2DM.